2012
DOI: 10.1186/1471-2229-12-85
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the sucrose synthase gene family in cotton: structure, phylogeny and expression patterns

Abstract: BackgroundIn plants, sucrose synthase (Sus) is widely considered as a key enzyme involved in sucrose metabolism. Several paralogous genes encoding different isozymes of Sus have been identified and characterized in multiple plant genomes, while limited information of Sus genes is available to date for cotton.ResultsHere, we report the molecular cloning, structural organization, phylogenetic evolution and expression profiles of seven Sus genes (GaSus1 to 7) identified from diploid fiber cotton (Gossypium arbore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 64 publications
12
77
0
Order By: Relevance
“…In the structural evolutionary history of gene families, exon/intron insertion or deletion or both events between the paralogs may be happening to some extent and represent attribution features [28]. In the present study, the number and position of introns of six putative Sus genes were different in size but showed parallel positions and were flanked by GT-AG boundaries, highly consistent with rubber [8], poplar [15] and cotton [13]. In addition, we also found that the six putative CitSus isozymes were evenly distributed into the three plant Sus groups (SusI, SusII and SusIII) (Figure 2), similar with other plant Sus gene distribution [8], [11], [13], [15], [19].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the structural evolutionary history of gene families, exon/intron insertion or deletion or both events between the paralogs may be happening to some extent and represent attribution features [28]. In the present study, the number and position of introns of six putative Sus genes were different in size but showed parallel positions and were flanked by GT-AG boundaries, highly consistent with rubber [8], poplar [15] and cotton [13]. In addition, we also found that the six putative CitSus isozymes were evenly distributed into the three plant Sus groups (SusI, SusII and SusIII) (Figure 2), similar with other plant Sus gene distribution [8], [11], [13], [15], [19].…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, the number and position of introns of six putative Sus genes were different in size but showed parallel positions and were flanked by GT-AG boundaries, highly consistent with rubber [8], poplar [15] and cotton [13]. In addition, we also found that the six putative CitSus isozymes were evenly distributed into the three plant Sus groups (SusI, SusII and SusIII) (Figure 2), similar with other plant Sus gene distribution [8], [11], [13], [15], [19]. Moreover, the three C. unshiu Sus genes identified by Komatsu et al [20] were clustered into two Sus dicot sub-groups in the present study, similar to a previously constructed phylogenetic tree [20].…”
Section: Discussionsupporting
confidence: 70%
“…It was reported that the expression level of Sus 1 was low in 10 DPA fiber [43], which was perfectly consistent with the finding in this study. Although GhSus3 (U73588) has been demonstrated to play an important role in ovule development and fiber cell initiation, the functional characterization of Sus genes however was limited [43]. The development of fiber is a complex process, and there are some overlapping processes among each developmental stage.…”
Section: Q Miao Et Al American Journal Of Plant Sciencessupporting
confidence: 82%
“…This classification was corroborated a number of subsequent studies, and three groups were respectively named as the Class I, Class II, and Class III groups [2,28,56]. Later, the Class I group can be further divided into a monocot subgroup and a eudicot subgroup, as these two subgroups were obviously distinct from each other in phylogenetic trees constructed by dozens of plant SS gene families.…”
Section: Discussionmentioning
confidence: 57%